2016
DOI: 10.1088/0741-3335/59/1/014015
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and spatial characterisation of laser-driven positron beams

Abstract: The generation of high-quality relativistic positron beams is a central area of research in experimental physics, due to their potential relevance in a wide range of scientific and engineering areas, ranging from fundamental science to practical applications. There is now growing interest in developing hybrid machines that will combine plasma-based acceleration techniques with more conventional radio-frequency accelerators, in order to minimise the size and cost of these machines. Here we report on recent expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…We disagree with this statement. The applicability of LWFA-driven positrons to advanced accelerator concepts is currently subject of investigation, and our recent work [3,4,6], together with that of independent groups [7,8], confirms that there is significant potential in this area. We have also confirmed that such positron beams can be used for some specific studies in laboratory astrophysics, and we have already experimentally measured plasmalike behavior of LWFAdriven electron-positron beams [9][10][11][12].…”
mentioning
confidence: 62%
“…We disagree with this statement. The applicability of LWFA-driven positrons to advanced accelerator concepts is currently subject of investigation, and our recent work [3,4,6], together with that of independent groups [7,8], confirms that there is significant potential in this area. We have also confirmed that such positron beams can be used for some specific studies in laboratory astrophysics, and we have already experimentally measured plasmalike behavior of LWFAdriven electron-positron beams [9][10][11][12].…”
mentioning
confidence: 62%
“…An alternative method for the generation of neutral electron-positron plasmas has been identified in exploiting the quantum cascade initiated by a laser-driven electron beam propagating through a solid target. Even though this method suffers from the difficulty of generating cold populations and confining them, promising results have been obtained in different configurations [11,12,13,14,15,16,17], with, to-date, the first experimental demonstration of a neutral electron-positron beam able to show collective behaviour [14,17]. The details of the laser-driven generation of neutral electron-positron beams (EPBs) can be found elsewhere [13,14,15,16]; in this paper, we will instead focus our attention on some of the main experimental issues involved in detecting the dynamics of these objects, when they propagate through a background electron-ion plasma.…”
Section: Introductionmentioning
confidence: 99%
“…The rear side of the gas-cell was covered with a LANEX scintillator screen, in order to provide information about the spatial distribution of the EPB with and without the second gas-cell. During free propagation, the EPB presents a smooth spatial profile, well approximated by a super-gaussian [37]. Finally, a magnetic spectrometer allowed separating and measuring the spectrum of the electrons and positrons in the beam on each laser shot.…”
mentioning
confidence: 99%